PEPSI: The high‐resolution ichelle spectrograph and polarimeter for the Large Binocular Telescope. Issue 4 (June 2015) - Strassmeier, K.G.; Ilyin, I.; Järvinen, A.; Weber, M.; Woche, M.; Barnes, S. I.; Bauer, S.‐M.; Beckert, E.; Bittner, W.; Bredthauer, R.; Carroll, T. A.; Denker, C.; et al.
Abstract PEPSI is the bench‐mounted, two‐arm, fibre‐fed and stabilized Potsdam Echelle Polarimetric and Spectroscopic Instrument for the 2×8.4 m Large Binocular Telescope (LBT). Three spectral resolutions of either 43 000, 120 000 or 270 000 can cover the entire optical/red wavelength range from 383 to 907 nm in three exposures. Two 10.3k×10.3k CCDs with 9‐µm pixels and peak quantum efficiencies of 94–96 % record a total of 92 échelle orders. We introduce a new variant of a wave‐guide image slicer with 3, 5, and 7 slices and peak efficiencies between 92–96 %. A total of six cross dispersers cover the six wavelength settings of the spectrograph, two of them always simultaneously. These are made of a VPH‐grating sandwiched by two prisms. The peak efficiency of the system, including the telescope, is 15 % at 650 nm, and still 11 % and 10 % at 390 nm and 900 nm, respectively. In combination with the 110 m2 light‐collecting capability of the LBT, we expect a limiting magnitude of ≈20th mag in V in the low‐resolution mode. The R = 120 000 mode can also be used with two, dual‐beam Stokes IQUV polarimeters. The 270 000‐mode is made possible with the 7‐slice image slicer and a 100‐µm fibre through a projected sky aperture of 0.74″, comparable to the median seeing of the LBT site. The 43 000‐mode with 12‐pixel sampling per resolution element is our bad seeing or faint‐object mode. Any of the three resolution modes can either be used with sky fibers for simultaneous sky exposures or with light from a stabilized Fabry‐Pérot étalon for ultra‐precise radial velocities. CCD‐image processing is performed with the dedicated data‐reduction and analysis package PEPSI‐S4S. Its full error propagation through all image‐processing steps allows an adaptive selection of parameters by using statistical inferences and robust estimators. A solar feed makes use of PEPSI during day time and a 500‐m feed from the 1.8 m VATT can be used when the LBT is busy otherwise. In this paper, we present the basic instrument design, its realization, and its characteristics. Some pre‐commissioning first‐light spectra shall demonstrate the basic functionality. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)